Simulation Tool for Assessing Driving Strategies for Electric Racing Vehicles. - Rosas-Cervantes, Daniel; Fernández-Ramos, José (MDPI, 2023)
This article deals with the development of a simulation tool for evaluating the energy consumption of an electric racing vehicle. The tool was carried out in the Matlab/Simulink environment and is based on the equations that govern the dynamics of the vehicle. All the systems of an electric vehicle were modelled: motor, battery, controller, bodywork, etc., as well as the characteristics of the competition circuit. The tool allows us to choose the input variable of the simulation between motor torque, motor voltage, battery power or vehicle speed and provides the values of all relevant physical variables to evaluate the performance of the vehicle. To evaluate the tool, a test was carried out with a real vehicle on a test circuit and both were modelled. The simulation results were compared with the experimental data obtained in the real test and it was verified that the simulation tool provides results that are very close to the real ones. In order to show the performance of the tool, simulations of different driving strategies were carried out and the results of energy consumption in each of them were obtained, allowing us to choose which of them is the most efficient.
Keywords: Industria automovilística; Vehículos eléctricos; Modelling; Light electric vehicle; Simulation tool; Energy efficiency; Driving strategies